2022
DOI: 10.1002/ecs2.4170
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability and uncertainty of soil nitrogen across the conterminous United States at different depths

Abstract: Soil nitrogen (N) is an important driver of plant productivity and ecosystem functioning; consequently, it is critical to understand its spatial variability from local‐to‐global scales. Here, we provide a quantitative assessment of the three‐dimensional spatial distribution of soil N across the United States (CONUS) using a digital soil mapping approach. We used a random forest‐regression kriging algorithm to predict soil N concentrations and associated uncertainty across six soil depths (0–5, 5–15, 15–30, 30–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 78 publications
0
3
1
Order By: Relevance
“…However, despite the observation that polyploids tended to have more reduced photosynthetic activity relative to diploids when both N and P were at ambient levels, differences among cytotypes in terpene production and photosynthetic rates were not less apparent under enriched nutrient conditions. Furthermore, in contrast to our predictions, larger GS cytotypes were not more efficient than smaller GS cytotypes at incorporating N and P into photosynthates or biomass (although under ambient conditions, hexaploids were the most efficient at incorporating nutrients into biomass, which might be related to them being more adapted to nutrient-poor soils; Smith et al, 2022). Cumulatively, these results suggest that larger GS cytotypes might use resources more efficiently (as seen in hexaploids) and/or partition resources between the genome and other costly factions (such as photosynthesis and defense) to lessen genome-material-cost constraints but T A B L E 4 Results from fixed-effects ANOVA models for the effects of cytotype (diploid = 2x, tetraploids = 4x, hexaploid = 6x), soil N:P treatments (ambient N:P = A, enriched N:P = E), their interaction, and population of origin nested within cytotype on the concentrations of foliar total terpenes, monoterpenes, diterpenes, and sesquiterpenes (all logtransformed).…”
Section: Genetic Mechanisms Might Minimize Material-cost Constraintscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, despite the observation that polyploids tended to have more reduced photosynthetic activity relative to diploids when both N and P were at ambient levels, differences among cytotypes in terpene production and photosynthetic rates were not less apparent under enriched nutrient conditions. Furthermore, in contrast to our predictions, larger GS cytotypes were not more efficient than smaller GS cytotypes at incorporating N and P into photosynthates or biomass (although under ambient conditions, hexaploids were the most efficient at incorporating nutrients into biomass, which might be related to them being more adapted to nutrient-poor soils; Smith et al, 2022). Cumulatively, these results suggest that larger GS cytotypes might use resources more efficiently (as seen in hexaploids) and/or partition resources between the genome and other costly factions (such as photosynthesis and defense) to lessen genome-material-cost constraints but T A B L E 4 Results from fixed-effects ANOVA models for the effects of cytotype (diploid = 2x, tetraploids = 4x, hexaploid = 6x), soil N:P treatments (ambient N:P = A, enriched N:P = E), their interaction, and population of origin nested within cytotype on the concentrations of foliar total terpenes, monoterpenes, diterpenes, and sesquiterpenes (all logtransformed).…”
Section: Genetic Mechanisms Might Minimize Material-cost Constraintscontrasting
confidence: 99%
“…While we cannot assess this possibility and contribution using field‐collected maternal lines, we did find that population of origin had a significant effect on growth, metabolic, and nutrient‐use attributes. Thus, hexaploids in general might not have been as negatively affected as tetraploids (or even diploids) in terms of biomass accumulation under ambient‐N conditions if hexaploids are pre‐adapted to tolerate the more N‐poor conditions of the Great Plains versus the less nitrogen‐poor conditions of the Great Lakes and eastern regions (Smith et al, 2022) where tetraploids and diploids primarily occur, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In arable land, higher NT content and NTS at the depth of 35-45 cm were found in DV (FLgl), and KE (CMst), which could be related to nitrate leaching from the topsoil [66]. A study from the USA reported the variability and uncertainty of NT content and NTS in the soil profile [67]. The TN content is directly influenced by soil organic matter [68].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the realized cost of N acquisition likely varies depending on a microbe's environmental context and life history adaptations (i.e., substrate flux, mode of metabolism, resource allocation, motility, etc.). For instance, the dynamic nature of the bioavailable N pool as well as spatial heterogeneity of geochemistry in structured environments such as soils (Smith et al, 2022 ) may shape the relative distributions of N acquisition strategies within natural microbial communities. Several outstanding questions in this regard are: (i) How prevalent are different N acquisition strategies among microbes across environmental systems?…”
Section: Introductionmentioning
confidence: 99%